Spike-Stalk Injection Method Causes Extensive Phenotypic and Genotypic Variations for Rice Germplasm - Hu, Yuanyi; Mao, Bigang; Xia, Yumei; Peng, Yan; Zhang, Dan; Tang, Li; Shao, Ye; Li, Yaokui; Zhao, Bingran (Frontiers in Plant Science, 2020)
Genetic diversities or favorable genes within distantly related species are the important resources for crop genetic improvement and germplasm innovation. Spike-Stalk injection method (SSI) has long been applied in rice genetic improvement by directly introducing genetic materials from non-mating donor species, while its inheritance patterns and the underlying mechanisms are poorly elucidated. In this study, a rice variant ERV1 with improved yield-related traits was screened out in the way of introducing genomic DNA of Oryza eichingeri (2n=24, CC genome) into RH78 (Oryza sativa L. 2n=24, AA genome) using SSI method. Genome-wide comparison revealed that the genomic heterozygosity of ERV1 was approximately 8-fold higher than RH78. Restriction-site associated DNA sequencing technology (RAD-seq) and association analysis of the ERV1 inbred F2 population identified 5 quantitative trait loci (QTLs) regions responsible for these yield-related traits, and found that genomic heterozygosity of ERV1 inbred lines was significantly lower than ERV1, while spontaneous mutation rate of the ERV1 inbred lines was significantly higher than ERV1. Our results preliminarily uncovered the inheritance patterns of SSI variant rice, and the potential genomic regions for traits changes, which yielded novel insights into the mechanisms of SSI method, and may accelerate our understanding of plant genome evolution, domestication, and speciation in nature.